INDIGENOUS USES AND PHYTOCHEMICAL CONTENTS OF PLANTS USED IN THE TREATMENT OF MENSTRUAL DISORDERS AND AFTER- CHILD BIRTH PROBLEMS IN ABEOKUTA SOUTH LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - Kadiri, M; Ojewumi, A W; Onatade, T N (Journal of Drug Delivery and Therapeutics, 2015)
A survey of plants used for the treatment of menstrual disorders and after-child birth problems was conducted in Abeokuta South Local Government. Hundred (100) questionnaires were administered using multi stage sampling method on traditional herbal practitioners. Ethnobotanical information such as, plants and plant parts used, methods of extraction used and mode of administration of the herbal preparations of these plants were requested. Also, phytochemical contents of the most frequently mentioned plants were determined. Data were subjected to Analysis of variance (ANOVA) with probability set at p